Architecture of Dispatched, a Transmembrane Protein Responsible for Hedgehog Release - Luo, Yitian; Wan, Guoyue; Zhou, Xuan; Wang, Qiuwen; Zhang, Yunbin; Bao, Juan; Cong, Yao; Zhao, Yun; Li, Dianfan (Frontiers in Molecular Biosciences, 2021)
The evolutionarily conserved Hedgehog (Hh) signaling pathway is crucial for programmed cell differentiation and proliferation. Dispatched (Disp) is a 12-transmembrane protein that plays a critical role in the Hedgehog (Hh) signaling pathway by releasing the dually lipidated ligand HhN from the membrane, a prerequisite step to the downstream signaling cascade. In this study, we focus on the Disp from water bear, a primitive animal known as the most indestructible on earth. Using a zebrafish model, we show that the water bear homolog possesses Disp function. We have solved its structure to a 6.5-Å resolution using single-particle cryo-electron microscopy. Consistent with the evolutional conservation of the pathway, the water bear Disp structure is overall similar to the previously reported structures of the fruit fly and human homologs. Although not revealing much detail at this resolution, the water bear Disp shows a different conformation compared to published structures, suggesting they may represent different functional snapshots.